Determination of full set material constants of [011](c) poled 0.72Pb(Mg(1/3)Nb(2/3))O(3)-0.28PbTiO(3) single crystal from one sample - Li, Shiyang (American Institute of Physics, 2014)
0.72Pb(Mg(1/3)Nb(2/3))O(3)-0.28PbTiO(3) single crystals poled along [011](c) have macroscopic orthorhombic mm2 symmetry. There are total 17 independent material coefficients for this symmetry so that the determination of self-consistent full matrix data is extremely difficult because many samples are needed and there is a large property variation from sample to sample. To overcome this self-consistency difficulty, we have developed a combined ultrasonic pulse-echo and impedance spectroscopy method, which can extract all coefficients from only one small sample. This method is especially useful for piezoelectric materials whose properties are strongly dependent on geometry and for crystals with only limited size available.